PRINCIPLES OF ELECTRICAL IMPEDANCE CALCULATING OF OSCILLATING PIEZOCERAMIC DISK IN THE AREA OF MEDIUM FREQUENCIES - Bazilo, C. V. (Radio Electronics, Computer Science, Control, 2018)
Context. The relevance of the use of various functional elements of piezoelectronics in power and informational systems is due, above all, to their high reliability. The final goal of mathematical modeling of the vibrating piezoelectric elements physical condition is a qualitative and quantitative description of characteristics and parameters of existing electrical and elastic fields. Objective. The aim of this work is to calculate the electrical impedance of oscillating piezoelectric disk in the mid-frequency range. Method. At sufficiently general initial assumptions a mathematical description of the electrical impedance of the oscillating thin piezoceramic disk with end surfaces continuous covering by electrodes in vacuum is obtained. It is shown that electric impedance is determined by the averaged values of the components of piezoceramics material particles displacement vector. Results. Expression for electrical impedance calculating of the oscillating piezoceramic disk at middle frequencies is built, where the disk’s material particles displacement vector is almost completely determined by the radial component. Conclusions. As a result of research of real device’s mathematical model a set of geometrical, physical and mechanical and electrical parameters of a real object can be determined which provides realization of technical parameters of piezoelectric functional element specified in technical specifications. This significantly reduces the time and cost of new functional elements of piezoelectronics development. Prospects for further research can be defined as the construction of technology for calculating of transformation coefficients in piezoelectric transformer with several secondary electrical circuits.